Some Methodological Insights from a Reflexive "Insider" Ethnography of Shiatsu Practice. (August 2022) - Spurr, Sue; Barbour, Rosaline S.; Draper, Jan
Presented as a collaborative reflexive account, this article has evolved through a series of discussions between the first author—who carried out an "insider" ethnography of Shiatsu practice—and her two supervisors. We highlight the challenges that she faced as an ethnographer in a field already familiar to the researcher and demonstrate how it was possible to use this tension to advantage in crafting an enhanced methodological approach. Drawing upon Bourdieu's (1996, 24) notion of "forgetfulness of self, " we explore how the first author was able to harness and hone her key abilities, disposition, and innate knowledge as an experienced Shiatsu practitioner in order to forge a blended approach. Finally, the article suggests that this approach, based on sensitive skills involving "listening, " intuition, and touch—the essence of Shiatsu—can enhance ethnographic practice in general.